BEAUTY ECONOMY IN THAILAND: PHENOMENON, INFLUENCE AND FUTURE DEVELOPMENT - Linfan; Lavanchawee Sujarittanonta (The American Journal of Interdisciplinary Innovations and Research, 2024)
This article aims to study the economic phenomenon of beautiful women in Thailand, including its definition, characteristics, impact, and future development. Thailand, often hailed for its stunning landscapes and rich cultural heritage, is also renowned for its exquisite beauty. The allure of Thai beauties has transcended personal emotions to become a significant economic force in the country. Through an in-depth analysis of Thailand's beauty economy, this paper explores its impact on Thai society, economy, and culture, shedding light on the profound influence of beauty in this Southeast Asian nation. Thai beauties have long been the dream objects of men all over the world, attracting tourists and enthusiasts alike. However, their influence extends beyond admiration, as it has played a pivotal role in Thailand's tourism, entertainment, and labor markets. This influence has not only fuelled economic growth but has also had far-reaching effects on Thai society and culture (Norton 2001). As we delve into the intricate dynamics of the beauty economy, we aim to understand how it has shaped Thailand's identity and economy. Furthermore, we will offer insights and suggestions for promoting the healthy and sustainable development of this remarkable economic phenomenon.